"If you don't have a word for something, you may doubt whether it's even real" – how individuals with borderline personality disorder experience change. (17th November 2021) - Koivisto, Maaria; Melartin, Tarja; Lindeman, Sari
Abstract: Objective: : This study explored how psychological change was experienced and what treatment-related factors or events were perceived as supporting or hindering their process by individuals with borderline personality disorder. Methods: : Eight BPD sufferers attended a 40-session psychoeducational group intervention at a community mental health care center. At intervention end, personal experience of meaningful change was explored in an in-depth interview and data were content-analyzed. Change in BPD symptoms was assessed by the Borderline Personality Disorder Severity Index IV interview. Results: : The qualitative content analysis on subjectively perceived meaningful change yielded three core categories: (1) improved ability to observe and understand mental events, (2) decreased disconnection from emotions, emergence of new or adaptive emotional reactions and decrease in maladaptive ones, and (3) a new, more adaptive experience of self and agency. Accordingly, (1) learning and (2) normalizing emerged as the main categories of helpful treatment factors. In turn, treatment-related factors perceived as obstacles were: (1) aggression in the group, and (2) inflexibility. With respect to symptom change, four participants were considered clinically as remitted, and two showed a reliable change. Conclusions: : Long-term psychoeducational group therapy seems to enhance mentalization / metacognitive functioning and promote self (or personality) integration in BPD patients.